2012
DOI: 10.1177/1934578x1200700938
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Anticancer, and Antimicrobial Activities in vitro of the Heartwood Essential Oil of Cunninghamia lanceolata var. konishii from Taiwan

Abstract: This study investigated the chemical composition, anticancer, and antimicrobial activities in vitro of the essential oil isolated from the heartwood of Cunninghamia lanceolata var. konishii from Taiwan. The essential oil was isolated using hydrodistillation in a Clevenger-type apparatus, and characterized by GC-FID and GC-MS. Thirty-seven compounds were identified, representing 100% of the oil. The main components identified were cedrol (58.3%), -cedrene (11.8%), -terpineol (4.2%) and-cedrene (3.5%). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Our findings are in agreement with those of Ikeda and Fujita, who also found that the C. konishii wood essential oil comprised main pinene, selinene, limonene, α ‐terpinol, borneol and cedrol. In addition, Su et al also found that the main constituent of heartwood essential oil was cedrol (58.3%). Such result is in agreement with that of Su et al , who also found that the main constituent of leaf essential oil was α ‐pinene (36.4%).…”
Section: Resultsmentioning
confidence: 97%
“…Our findings are in agreement with those of Ikeda and Fujita, who also found that the C. konishii wood essential oil comprised main pinene, selinene, limonene, α ‐terpinol, borneol and cedrol. In addition, Su et al also found that the main constituent of heartwood essential oil was cedrol (58.3%). Such result is in agreement with that of Su et al , who also found that the main constituent of leaf essential oil was α ‐pinene (36.4%).…”
Section: Resultsmentioning
confidence: 97%
“…Cedar oil and its major components, β-cedrene, cedrol, and thujopsene, exert various biological activities, such as antiseptic, anti-inflammatory, antispasmodic, tonic, astringent, diuretic, sedative, insecticidal, and antifungal effects (Carroll et al, 2011;Dayawansa et al, 2003;Eller et al, 2014;Hori et al, 2012;Kagawa et al, 2003;Kim et al, 2013;Manter et al, 2007;Oh et al, 2011;Su et al, 2012;Yada et al, 2007). Therefore, these compounds are used globally as traditional medicines, as well as in soaps, shampoos, fragrances, and cosmetics (Bhatia et al, 2008).…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…We demonstrated the growth-inhibiting effects of cedrene derived from the essential oil of P. orientalis leaves against C. perfringens and E. coli. Cedrene is abundant in many plants such as Cephalaria lycica, C. scoparia, Coleus forskohlii, Cunninghamia lanceolata, Juniperus virginiana, and Haplophyllum acutifolium (9,20,(23)(24)(25)(26)(27), and it has antimicrobial and antileukemic effects (9,28,29). Taken together, P. orientalis leaf oil, in which cedrene is the major component, could be used as a selective inhibitor of harmful intestinal bacteria.…”
Section: )mentioning
confidence: 99%